2014
DOI: 10.1007/s00775-014-1122-9
|View full text |Cite
|
Sign up to set email alerts
|

A two-electron-shell game: intermediates of the extradiol-cleaving catechol dioxygenases

Abstract: Extradiol catechol ring-cleaving dioxygenases function by binding both the organic substrate and O2 at a divalent metal center in the active site. They have proven to be a particularly versatile group of enzymes with which to study the O2 activation process. Here, recent studies of homoprotocatechuate 2,3-dioxygenase (HPCD) are summarized with the objective of showing how Nature can utilize the enzyme structure and the properties of the metal and the substrate to select among many possible chemical paths to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 54 publications
3
43
0
Order By: Relevance
“…1. C2,3D are extradiol-cleaving dioxygenases that function by binding both the organic substrate and O 2 at a divalent metal center in the active site (Fielding, Lipscomb, & Que, 2014). X-ray analysis of crystallized C2,3D from P. putida proved a nonheme Fe(II) center in each of the four identical subunits forming the functional enzyme (Kita et al, 1997).…”
Section: Enzymes Of the Meta-ring Cleavage Pathwaysmentioning
confidence: 98%
“…1. C2,3D are extradiol-cleaving dioxygenases that function by binding both the organic substrate and O 2 at a divalent metal center in the active site (Fielding, Lipscomb, & Que, 2014). X-ray analysis of crystallized C2,3D from P. putida proved a nonheme Fe(II) center in each of the four identical subunits forming the functional enzyme (Kita et al, 1997).…”
Section: Enzymes Of the Meta-ring Cleavage Pathwaysmentioning
confidence: 98%
“…Cobalt and manganese have been used previously as robust probes to uncover necessary electronic structural properties and structure-activity relationships in other proteins. 3336 including superoxide dismutase, 3741 catechol dioxygenase, 42 myoglobin, 43,44 P 1B -type ATPases, 45 and metallothioneins. 46 Understanding the roles of nonheme metal ions beyond the Cu and Fe in native HCO and NOR will provide deeper insights into nature’s choice of metal ion and allow finer control of the activity beyond native enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…15, 17, 18, 32 In the past decade, our laboratories have used a variety of techniques to study the wild-type (WT) enzyme as well as active site variants in which important 2 nd -sphere residues were mutated. 2630, 3337 Biochemical studies have shown that His200 serves a variety of critical functions in the activation of dioxygen, among them acid/base catalysis. To further probe the importance of His200, we recently studied a variant, H200C, in which His200 was replaced by cysteine.…”
Section: Introductionmentioning
confidence: 99%